Organometallic and radical intermediates reveal mechanism of diphthamide biosynthesis - Dong, Min; Kathiresan, Venkatesan; Fenwick, Michael K; Torelli, Andrew T; Zhang, Yang; Caranto, Jonathan D; Dzikovski, Boris; Sharma, Ajay; Lancaster, Kyle M; Freed, Jack H; Ealick, Steven E; Hoffman, Brian M; et al. (Science (American Association for the Advancement of Science), 2018)
Diphthamide biosynthesis involves a carbon-carbon bond-forming reaction catalyzed by a radical S-adenosylmethionine (SAM) enzyme that cleaves a carbon-sulfur (C-S) bond in SAM to generate a 3-amino-3-carboxypropyl (ACP) radical. Using rapid freezing, we have captured an organometallic intermediate with an iron-carbon (Fe-C) bond between ACP and the enzyme's [4Fe-4S] cluster. In the presence of the substrate protein, elongation factor 2, this intermediate converts to an organic radical, formed by addition of the ACP radical to a histidine side chain. Crystal structures of archaeal diphthamide biosynthetic radical SAM enzymes reveal that the carbon of the SAM C-S bond being cleaved is positioned near the unique cluster Fe, able to react with the cluster. Our results explain how selective C-S bond cleavage is achieved in this radical SAM enzyme.